Serum cytokine pattern in young children with screening detected coeliac disease. (2nd January 2015) - Björck, S; Lindehammer, S R; Fex, M; Agardh, D
Summary: Coeliac disease is an autoimmune disease characterized by inflammation localized to the small bowel, but less is known about systemic signs of inflammation. The aim was to measure cytokines of the T helper 1 (Th1) and T helper 2 (Th2) cell patterns in children with screening-detected coeliac disease before and after treatment with a gluten-free diet. Serum samples selected before and after the start of a gluten-free diet from 26 3-year-old children diagnosed with biopsy-proven coeliac disease and from 52 matched controls were assayed in an multiplex enzyme-linked immunosorbent assay (ELISA) for the 10 cytokines: interferon (IFN)-γ, interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-8, IL-10, IL-12p70, IL-13 and tumour necrosis factor (TNF)-α. Among Th1 cytokines, IFN-γ and IL-12p70 were elevated significantly in children with coeliac disease compared to controls ( P < 0·001 and P = 0·001, respectively). Similar findings were demonstrated for the Th2 cytokines IL-5 ( P < 0·001), IL-10 ( P = 0·001) and IL-13 ( P = 0·002). No difference in cytokine levels between the two groups was found for TNF-α, IL-1β, IL-2, IL-4 and IL-8. After gluten-free diet, levels of IL-5, IL-12 and IL-10 decreased significantly ( P < 0·001, P = 0·002 and P = 0·007) and IFN-γ levels were reduced ( P = 0·059). Young children with coeliac disease detected by screening demonstrate elevated levels of serum cytokines at time of diagnosis. A prolonged systemic inflammation may, in turn, contribute to long-term complications known to be associated with untreated coeliac disease.